Green Synthesis of ZnO-AgNPs-CPE using Male Carica papaya Flower Extract for Antibacterial and Anti-inflammatory Activities - Thao, Truong Thi; Duangphachanh, Itphavanh; Tam, Khieu Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 41 No 2, 2025)
Recently, bimetallic nanoparticles, formed through the integration of two different metals, exhibit superior biological activity compared to monometallic nanoparticles due to synergistic effects and diverse mechanisms of action. In this study, nano Ag doped zinc oxide were synthesized using the ethanol extract of male Carica papaya flower (ZnO-AgNPs-CPE). The characteristics of the materials were determined by XRD, FTIR, SEM, and EDX methods.      ZnO-AgNPs-CPE are crystalline in nature, highly pure, stabilized by organic compounds present in the extract, thin spherical layers in the shape, and contain mainly Zn, Ag, and O components. The material shows strong antibacterial and antifungal activity against tested strains of Staphylococcus aureus , Escherichia coli , Pseudomonas aeruginosa , and Candida albicans . Furthermore, the material also exhibits anti-inflammatory activity with an IC 50 value of 54.4 μg/mL. The results indicate that ZnO-AgNPs can be synthesized using Carica papaya flower extract for effective antimicrobial and anti-inflammatory activities.